Impact of Sowing Technologies of Wheat Cultivation in Ferozepur, Punjab - Anand Gautam,; Gurjant Singh Aulakh, (Indian Journal of Extension Education, 2022)
A field experimentation was carry out with four different sowing methods on different three locations of district of Ferozepur (Punjab) during 2021-22, to detect the most applicable method of wheat sowing after rice crop in district Ferozepur of Punjab state. The experiment was carried out including Broadcasting + Mulcher, PAU Happy Seeder, Zero Till Drill and Super Seeder. The utmost grain yield was obtained by PAU Happy Seeder (54.45 q/ha) sowing method as compared to Brodcasting + Mulcher (51.85 q/ha), Super Seeder (49.15 q/ha) and Zero Drill (45.95 q/ha). However, the ratio of benefit-cost was higher by PAU Happy Seeder (3.71:1) as compared to as compared to Brodcasting + Mulcher (3.51:1), Zero Drill (2.76:1) and Super Seeder (2.38:1). The better net return obtained from PAU Happy Seeder Rs. 120602.50/ha as compared to Brodcasting + Mulcher (109548.75/ha), Super Seeder (95236.25/ha) and Zero Drill (93055.00/ha). The grain yield by PAU Happy Seeder method of sowing was higher as well as it successful to produce better net return and benefits of cost ratio. PAU Happy Seeder technology provided timely sowing operation of wheat and scope against burning of paddy residue in Punjab.